Smoking and the Business Cycle: Evidence from Germany - Micha Kaiser; Mirjam Reutter; Alfonso Sousa-Poza; Kristina Strohmaier (Institute of Labor Economics (IZA), 2017)
In this paper, we use data from the German Socio-Economic Panel to investigate the effect on cigarette consumption of macro-economic conditions in the form of regional unemployment rates. The results from our panel data models, several of which control for selection bias, indicate that the propensity to become a smoker increases significantly during an economic downturn, with an approximately 0.7 percentage point increase for each one percentage point rise in the unemployment rate. Conversely, conditional on the individual being a smoker, cigarette consumption decreases during recessions, with a one percentage point increase in the regional unemployment rate leading to an up to 0.8 percent decrease in consumption.
Keywords: E32; I12; J22; 330; business cycle; smoking; unemployment